Protective Effect of Commonly Used Foods and Natural Products against COVID-19 - Mustafa, Faheem; Ali, Waffa; Noor, Remesah; Talat, Aiza; Maqsood, Mahnoor; Tahir, Hafsa; Zeeshan, Mouvez; Umar, Rabiatul Adawiyah Binti; Krishnasamy, Shanthi; Taib, Wan Rohani Wan; Baig, Atif Amin (BioScientific Review, 2024)
COVID-19 caused by the SARS-COV-2 virus has swiftly turned into a pandemic, leading to an ongoing health crisis worldwide. This disease has a zoonotic origin, and its symptoms range from asymptomatic, mild to severe, potentially leading to death. Given its pandemic nature, researchers around the world have expedited efforts to find the treatment. While synthetic drugs have been developed for treatment, their efficacy is still under evaluation, and their side effect is the primary concern. This situation necessitates the need to explore treatment options that are not only effective but also safe. Natural products could help COVID-19 prevention and treatment given their historical role in the treatment of other viruses such as HIV, MERS-CoV, and influenza. This study aims to evaluate the potential role of natural products against COVID-19, their mechanisms of action, and previous use against other viruses. This study aims to evaluate the potential role of natural products against COVID-19, their mechanisms of action, and previous use against other viruses. The comprehensive review focuses on natural products such as ginger, garlic, clove, black pepper, red pepper, black seeds, honey, turmeric, onion, ginseng, and thyme. The findings aim to contribute valuable insights to the development of anti-COVID-19 natural products.